VOICING THE VOICELESS: DESPAIR AND HOPES IN MIGRANT WORKERS’ SELECTED DIGITAL POEMS - Brameswari, Catharina; Iskarna, Tatang; Wijaya, Edith Nazaretha Putri (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2024)
This research scrutinises six digital poems written by migrant workers from Indonesia, India, the Philippines, China, and Bangladesh. In their digital poems, the migrant workers honestly shared their experience and feelings in times of Covid-19. Based on the problems, this research was conducted to unveil the effect of the pandemic on the migrant workers’ life. In conducting this research, the researchers use library research method and collect the data through documentation. This research employs New Criticism to highlight the complex issues faced by the migrant workers. Furthermore, Subaltern theory plays crucial role in investigating the power relations depicted in the digital poems and how the migrant workers can empower themselves and speak up their minds. This study unmasks how the migrant workers voiced their problems through the choice of words, symbols, and elements of literature. In their poems, the migrant workers illustrate their anxiety, loneliness, sadness, depression, and how they badly miss their families and homes. In addition, this research also highlights the migrant workers’ struggle to overcome the complex situation during lockdowns in Singapore. In conclusion, the digital poems are essential for the migrant workers to accommodate their voices, promote solidarity, and share their collective experiences during the lockdowns.